FAKTOR - FAKTOR YANG MEMENGARUHI TAX AVOIDANCE PADA PERUSAHAAN MANUFAKTUR - Oktaviani, Oktaviani; Viriany, Viriany (Jurnal Paradigma Akuntansi, 2024)
This study aims to determine whether there is an effect of profitability, leverage and firm size on tax avoidance. This research uses secondary data for manufacturing companies obtained from the Indonesian Stock Exchange (IDX) in 2018-2020. This study used a descriptive research design and the sample data was selected using purposive sampling method. There are 210 data from 70 companies in the manufacturing sector. The data is processed using the EViews 12 SV application. The results of this study that profitability has a negative and insignificant effect on Tax Avoidance, Leverage has a positive and significant effect on Tax Avoidance and Firm Size has a positive and insignificant effect on Tax Avoidance.